2011
DOI: 10.1080/22054952.2011.11464064
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Generic Engineering Competencies

Abstract: This paper contributes to understanding of the generic engineering competencies required by engineers graduating in Australia and to competency theory. The Competencies of Engineering Graduates (CEG) Project was conducted to identify the generic engineering competencies required by engineers graduating in Australia. The methodology adapted a theoretical framework for understanding key competencies developed by the Defi nition and Selection of Competencies Project commissioned by the Organisation for Economic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 3 publications
2
28
0
Order By: Relevance
“…The participating students [7] and alumni represented 79% and 12% of their respective target populations. The number of alumni who participated was the most significant limitation, however, the responses gathered were in agreement with other global and national studies discussed below [11][12][13]. The age distribution ( Figure 4) was centred around 22 years of age, indicative of those approaching graduation and recent graduates; respondents above the age of 30 represented the majority of part-time students.…”
Section: Demographic Analysissupporting
confidence: 55%
See 3 more Smart Citations
“…The participating students [7] and alumni represented 79% and 12% of their respective target populations. The number of alumni who participated was the most significant limitation, however, the responses gathered were in agreement with other global and national studies discussed below [11][12][13]. The age distribution ( Figure 4) was centred around 22 years of age, indicative of those approaching graduation and recent graduates; respondents above the age of 30 represented the majority of part-time students.…”
Section: Demographic Analysissupporting
confidence: 55%
“…Passow"s longitudinal study on ABET competencies found a statistically-significant top tier of competencies comprised of teamwork, communication, data analysis and problem solving [13]. Male"s Australian study similarly highlighted communication related skills; working in team; managing self; solving problems amongst the top ranked skills [12]. Both these studies provide support for the rating of these skills given by alumni.…”
Section: Full-time Students and Alumni Comparisonmentioning
confidence: 49%
See 2 more Smart Citations
“…We argue that these new perspectives for understanding engineers' practice and learning will contribute to the development of these 'emerging professionals', by providing a different way of understanding practice and the learning entwined in this practice. This perspective is in distinct contrast to the more common use of 'traditional' approaches to understanding engineer's work -as a set of competencies or skills and knowledge (see for example, Male, Bush and Chapman, 2011). It moves away from models of continuing professional learning which assume that the professional is in 'deficit' and has a lack of certain skills and knowledge (Boud and Brew, 2012).…”
Section: Introductionmentioning
confidence: 86%